Unified routing protocol based on passive bandwidth measurement in heterogeneous WMNs. Issue 15 (3rd June 2016) - Li, Zhimin; Wang, Hai; Dong, Chao; Wu, Fan; Yu, Weibo
Abstract: The past few years have witnessed a surge of wireless mesh networks (WMNs)‐based applications and heterogeneous WMNs are taking advantage of multiple radio interfaces to improve network performance. Although many routing protocols have been proposed for heterogeneous WMNs, most of them mainly relied on hierarchical or cluster techniques, which result in high routing overhead and performance degradation due to low utilization of wireless links. This is because only gateway nodes are aware of all the network resources. In contrast, a unified routing protocol (e.g., optimal link state routing (OLSR)), which treats the nodes and links equally, can avoid the performance bottleneck incurred by gateway nodes. However, OLSR has to pay the price for unification, that is, OLSR introduces a great amount of routing overhead for broadcasting routing message on every interface. In this paper, we propose unified routing protocol (URP), which is based on passive bandwidth measurement for heterogeneous WMNs. Firstly, we use the available bandwidth as a metric of the unification and propose a low‐cost passive available bandwidth estimation method to calculate expected transmission time that can capture the dynamics of wireless link more accurately. Secondly, based on the estimated available bandwidth, we propose a multipoint relays selection algorithm to achieve higher transmission ability and to help accelerate the routing message diffusion. Finally, instead of broadcasting routing message on all channels, nodes running URP transmit routing message on a set of selected high bandwidth channels. Results from extensive simulations show that URP helps improve the network throughput and to reduce the routing overhead compared with OLSR and hierarchical routing. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A Unified Routing Protocol (URP) based on passive bandwith measurement is proposed for heterogeneous WMNs. URP selects Multipoint Relays based on the available bandwidth to reduce overhead of redundant transmissions as well as accelerate the transmission of routing message. Meanwhile, URP manages to reduce the routing overhead and improve the throughput by sending routing packets on a set of selected high bandwidth channels, instead of broadcasting them on all the channels.